Odpowiedzi

2010-03-10T17:50:54+01:00
D)(6×0,2-8×0,1-0,7)-(6,9+0,2-5×0,1)+1,8= (1,2-0,8-0,7)-(7,1-0,5)+1,8=
-0,3-6,6+1,8=-6,9+1,8=-5,1

e) nie wiem xddd
Najlepsza Odpowiedź!
2010-03-10T17:52:49+01:00
D) (6a-8b-0,7)-(6,9+a-5b)+1,8 dla a=0,2 b=0.1
6a-8b-0,7 - 6,9-a+5b +1,8=
5a-3b -5,8
5* 0,2 - 3* 0,1 - 5,8 = 1 - 0,6 -5,8=-5,4
e)1/2abc-(4ab+2abc)+(-bc+5abc) dla a=-2 b=1/2 c=-4
1/2abc - 4ab-2abc -bc+5abc = 3 i 1/2abc - 4ab - bc = 3 i 1/2 * (-2)(-4)(1/2) - 4 * (-2)(1/2) - (1/2)*(-4)= 3i1/2 * 4 - (4*(-1)) +2 = 14 +4+2=20